Post-Asian economic crisis environment for foreign direct investments : multinational perceptions (service-oriented). - Chong, Kok Peng. (2008)
This paper examines the Post-Asian Economic Environment for Foreign Direct Investment in the Service Industry. It assesses the general investment environment, investment factors and the major trends affecting the service industry.Issues for further research are also discussed.